IS COLONIAL CINEMA POSSIBLE IN POLAND THESE DAYS? THE CASE OF PANI Z UKRAINY BY PAWEŁ ŁOZIŃSKI - Dabert, Dobrochna (Porównania, 2013)
The text provides a critical analysis of Paweł Łoziński’s film Pani z Ukrainy (2002) carried out from the perspective of postcolonial criticism. Łoziński, who wanted to create a warm psychological portrait of a Gastarbeiterin from Ukraine, thoughtlessly uses linguistic and customary behaviour by means of which he emphasises the diffrences instatus between him and the protagonist. The particular creative metod used by the documentarian which consists in introducing the film maker himself as the second character in the film, brought about a sharp image of inequality between the film maker (the owner of the house and the employer) who is invisible to the viewer and the Ukrainian who remains closely watched through the camera. The structure of the film is only seemingly based on a conversation. In fact, it is rather a „hearing” of the housekeeper which contributes to expressing the inequality of the positions of the two interlocutors. This image from the renowned documentarian can be treated as evidence that there exists the temptation to have a depreciative, exclusive and patronising attitude which is the result of a colonial but also colonising past.